ANALISIS PENGARUH CITRA MEREK DAN HARGA TERHADAP KEPUASAN KONSUMEN MELALUI KEPUTUSAN PEMBELIAN SEPATU OLAHRAGA MEREK ADIDAS DI KOTA PEKANBARU - safirma Raffi; Nursanti Aida; Noviasari Henni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This research aims to find out, (1) the effect of Brand Image on purchasing decisions, (2) the effect of price on purchasing decisions, (3) the influence of purchasing decisions on consumer satisfaction, (4) the influence of Brand Image on consumer satisfaction through purchasing decisions, (5) the influence of price on consumer satisfaction through purchasing decisions. The object of this research is Adidas sporth shoes consumers in Pekanbaru City. This research used Non probality sample and use accidental sample to chouse the sample. This research used SPSS as a data analysis method. Based on the results of testing, Brand Image has a positive and significant influence on purchasing decisions, Price has a positive and significant influence on purchasing decisions, Purchasing decisions have a positive and significant influence on consumer satisfaction, Brand Image has a positive and significant influence on consumer satisfaction through variable purchasing decisions, Price has a positive and significant influence on consumer satisfaction through variable purchasing decisions.Keyword: Brand Image, Price, Purchase Decision, Consumer Satisfaction